2018
DOI: 10.1038/s41467-018-03231-x
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II Subunit S overexpression increases the efficiency of water use in a field-grown crop

Abstract: Insufficient water availability for crop production is a mounting barrier to achieving the 70% increase in food production that will be needed by 2050. One solution is to develop crops that require less water per unit mass of production. Water vapor transpires from leaves through stomata, which also facilitate the influx of CO2 during photosynthetic assimilation. Here, we hypothesize that Photosystem II Subunit S (PsbS) expression affects a chloroplast-derived signal for stomatal opening in response to light, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
154
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(165 citation statements)
references
References 46 publications
11
154
0
Order By: Relevance
“…Ci would be expected to lead to a reduction in photosynthesis but, interestingly, these plants were able to maintain CO2 assimilation rates equal to or higher than control plants resulting in an improvement in iWUE. A similar improvement in iWUE was seen in plants overexpressing the NPQ related protein, PsbS 38 . It was shown that light-induced stomatal opening was reduced in these plants which had a more oxidized QA pool, which has been proposed to act as a signal in stomatal movement 39 .…”
Section: Discussionsupporting
confidence: 60%
“…Ci would be expected to lead to a reduction in photosynthesis but, interestingly, these plants were able to maintain CO2 assimilation rates equal to or higher than control plants resulting in an improvement in iWUE. A similar improvement in iWUE was seen in plants overexpressing the NPQ related protein, PsbS 38 . It was shown that light-induced stomatal opening was reduced in these plants which had a more oxidized QA pool, which has been proposed to act as a signal in stomatal movement 39 .…”
Section: Discussionsupporting
confidence: 60%
“…Szechy nska-Hebda, Kruk, Górecka, Karpi nska, and Karpi nski (2010) demonstrated that the local and systemic acquired acclimation (SAA) (Karpi nski et al, 1999) light acclimatory responses induced by episodes of excess lightare regulated by electrical signalling and are required for local and systemic NPQ adjustments (Białasek, Górecka, Mittler, & Karpi nski, 2017 (Białasek et al, 2017;Gilroy et al, 2016). Taken together, published results demonstrate that NPQ and PSII are key components in the retrograde regulation of SAA, SAR, CD, water-use efficiency, heat shock, as well as electrical and ROS signalling (Białasek et al, 2017;Gilroy et al, 2016;Głowacka et al, 2018;Karpi nski, Szechy nska-Hebda, Wituszy nska, & Burdiak, 2013;Kromdijk et al, 2016;Mateo et al, 2004;Mühlenbock et al, 2008;Szechy nska-Hebda et al, 2010).…”
Section: Introductionmentioning
confidence: 87%
“…Both stimulus‐induced systemic propagation of changes in NPQ and photosynthetic capacity, as well as electrical signalling, depended on calcium channel activity and extracellular respiratory burst regulated by the oxidase homolog D (RBOHD) (Białasek et al, ; Gilroy et al, ). Taken together, published results demonstrate that NPQ and PSII are key components in the retrograde regulation of SAA, SAR, CD, water‐use efficiency, heat shock, as well as electrical and ROS signalling (Białasek et al, ; Gilroy et al, ; Głowacka et al, ; Karpiński, Szechyńska‐Hebda, Wituszyńska, & Burdiak, ; Kromdijk et al, ; Mateo et al, ; Mühlenbock et al, ; Szechyńska‐Hebda et al, ).…”
Section: Introductionmentioning
confidence: 91%
“…If NPQ suppresses ROS formation this may lead to plants being more palatable to herbivores (Jänkänpää et al , ). One of the major players in NPQ regulation, PsbS was recently implicated in signalling stomatal movement (Głowacka et al , ). Such observations suggest even wider unappreciated roles for NPQ in plants in natural habitats.…”
Section: Quantifying the Role Of Npq In Plant Productivity: Diversitymentioning
confidence: 99%